2013
DOI: 10.1021/jp408788a
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Methyl Paraoxon in the Presence of Mg2+-Al3+ Mixed Oxides

Abstract: Al 3+ -Mg 2+ mixed oxides were prepared by coprecipitation and characterized with scanning electron microscopy (SEM), energy dispersive Xray fluorescence (EDXRF), temperature programmed desorption of CO 2 (CO 2 -TPD), and N 2 adsorption/desorption isotherms (BET and BJH methods). By increasing the MgO concentration up to 31.8% (w/w), X-ray diffraction (XRD) measurements suggested an incipient magnesium aluminate spinel (MgAl 2 O 4 ) phase. However, the spinel crystalline structure was obtained only after calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 44 publications
5
42
0
Order By: Relevance
“…It was concluded that most of the phosphorus compounds react with Al 2 O 3 to form AlPO 4 . Nome et al tested the Mg 2+ covered Al 2 O 3 in aqueous solution in the hydrolysis of phosphate diester ethyl 2,4‐dinitrophenyl phosphate (DEDNPP). Using coprecipitation method, they obtained Mg 2+ ‐Al 3+ mixed oxides and then examined their catalytic efficiency in hydrolyzing methyl paraoxon.…”
Section: Metal Oxides For Mimicking Phosphatases and Nucleasesmentioning
confidence: 99%
See 1 more Smart Citation
“…It was concluded that most of the phosphorus compounds react with Al 2 O 3 to form AlPO 4 . Nome et al tested the Mg 2+ covered Al 2 O 3 in aqueous solution in the hydrolysis of phosphate diester ethyl 2,4‐dinitrophenyl phosphate (DEDNPP). Using coprecipitation method, they obtained Mg 2+ ‐Al 3+ mixed oxides and then examined their catalytic efficiency in hydrolyzing methyl paraoxon.…”
Section: Metal Oxides For Mimicking Phosphatases and Nucleasesmentioning
confidence: 99%
“…Because of the chemical stability of P−O bonds, the decomposition of organophosphorus compounds remains a challenging problem . It would be helpful to develop the non‐enzyme catalysts which can destroy the large stockpiles of such compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Previous authors have proposed a similar mechanism to explain the hydrolysis mechanism of a variety of organophosphates and organic transformations in the presence of TiO 2 based materials or other metal oxides. 7,29,34,35 Our proposed mechanism is shown in Fig. 6.…”
Section: Degradation Of Methyl Parathionmentioning
confidence: 99%
“…XRD presented in figure 11. All the curves can be considered as a type IV isotherm, typical of mesoporous materials [25].…”
Section: Sample Characterizationmentioning
confidence: 99%